2023
DOI: 10.3390/metabo13040576
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Metabolic Profiles of “Indazole-3-Carboxamide” and “Isatin Acyl Hydrazone” (OXIZID) Synthetic Cannabinoids in a Human Liver Microsome Model Using UHPLC-QE Orbitrap MS

Abstract: Unregulated core structures, “isatin acyl hydrazones” (OXIZIDs), have quietly appeared on the market since China legislated to ban seven general core scaffolds of synthetic cannabinoids (SCs). The fast evolution of SCs presents clinical and forensic toxicologists with challenges. Due to extensive metabolism, the parent compounds are barely detectable in urine. Therefore, studies on the metabolism of SCs are essential to facilitate their detection in biological matrices. The aim of the present study was to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…According to their findings, the major metabolic pathways involved in MDMB-4en-PINACA metabolism are ester hydrolysis and hydroxylation, and up to nine metabolites can be detected in the serum [ 27 ]. Xiang et al also identified further ketone metabolites and special phase II metabolites [ 28 ]. Various clinical symptoms were reported after using MDMB-4en-PINACA, such as headaches, seizures, paranoia, anxiety, hallucinations, amnesia, mydriasis, nausea, and vomiting [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their findings, the major metabolic pathways involved in MDMB-4en-PINACA metabolism are ester hydrolysis and hydroxylation, and up to nine metabolites can be detected in the serum [ 27 ]. Xiang et al also identified further ketone metabolites and special phase II metabolites [ 28 ]. Various clinical symptoms were reported after using MDMB-4en-PINACA, such as headaches, seizures, paranoia, anxiety, hallucinations, amnesia, mydriasis, nausea, and vomiting [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to their findings, the major metabolic pathways involved in MDMB-4en-PINACA metabolism are ester hydrolysis and hydroxylation, and up to nine metabolites can be detected in the serum [27]. Xiang et al also identified further ketone metabolites and special phase II metabolites [28]. 4F-ABUTINACA-also known as N-(4-fluorobutyl)-APINACA or 4F-ABINACA, with the IUPAC name N-(1-adamantyl)-1-(4-fluorobutyl)indazole-3-carboxamide-is a fourth generation indazole-adamantyl-derived SCRA (Figure 1).…”
Section: Introductionmentioning
confidence: 99%